Air pollution and intracranial hemorrhage - Mervyn Lim Jun Rui; Jaclyn Tan; Benjamin Yong-Qiang Tan; Tseng Tsai Yeo; Vijay K Sharma (Annals of Indian Academy of Neurology, 2022)
Air pollution is a significant contributor to cardiovascular and cerebrovascular diseases. including intracranial hemorrhage (ICH). However, associations between air pollution, various pollutants, and ICH are complex and remain poorly understood. Limited data are available on the relationship between ICH and individual air pollutants. In this review, we present an overview of the current literature about ambient air pollutants that are believed to contribute towards ICH as well as possible underlying mechanisms.